Time-Evolving SED of MKN421: A Multi-Band View and Polarimetric Signatures - Fraga, Bernardo M. O.; Barres de Almeida, Ulisses; Gasparyan, Sargis; Giommi, Paolo; Sahakyan, Narek (Frontiers in Astronomy and Space Sciences, 2018)
The most detailed temporal studies of the emission from blazars are usually done by trying to obtain a dense, simultaneous coverage of the source over a large multi-wavelenght observational campaign. Although it is well know that correlations between multi-band emission present sizeable temporal lags in their correlated variability, such properties are usually neglected in the majority of observational studies, which model the evolution of source parameters over time by either building time-averaged SEDs (when data is scarce) or considering strictly simultaneous snapshots of the source along the spectrum. By making use of the resources and large database made available through the ASI Science Data Center (ASDC), we present a novel approach to the modelling of blazar emission whereby the multi-epoch SEDs for Mkn 421 are modelled considering the temporal lags between bands (both in short and long-timescales), as obtained by a detailed cross-correlation analysis, spanning data from radio to VHE gamma-rays from 2008 to 2014. In addition to that, long-term optical polarization data is used to aid and complement our physical interpretation of the state and evolution of the source.